Monitoring Method and North Florida Phenology of Pecan Nut Casebearer - Russell F. Mizell (EDIS)
The pecan nut casebearer, Acrobasis nuxvorella, is one of the most important early season pests of pecan. This document is ENY-707, one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2001. Revised: June 2004.